Quartz-enhanced photoacoustic spectroscopy in the terahertz spectral range - Votintsev, Alexey P.; Borisov, Alexey V. 1980-; Makashev, Didar R.; Stoyanova, Mariya Y.; Kistenev, Yury V. (Photonics)
Infrared laser photo-acoustic spectroscopy provides very high sensitivity of a gas sample analysis when high-power tunable laser radiation sources and resonant photo-acoustic detectors (PADs) are used. In the resonant PAD, the acoustic signal generated by absorbed laser radiation in a measurement chamber is amplified proportionally to a Q-factor of the acoustic resonator. But, compact tunable high-power lasers (with power above 100 mW) still are not widely spread in the terahertz spectral range. One of the ways to achieve an acceptable sensitivity of terahertz photoacoustic spectroscopy is using PADs with a very high Q-factor. The latter can be achieved using PAD with a quartz tuning fork. The current state in this field is presented in the review.